2020
DOI: 10.5539/ies.v13n4p27
|View full text |Cite
|
Sign up to set email alerts
|

Using Educational Robotics as a Cognitive Tool for ICT Teachers in an Authentic Learning Environment

Abstract: This study describes the theoretical foundations of a learning environment designed for an ICT teachers’ graduate level course, and presents a comprehensive analysis of the qualitative data acquired regarding the course’s implementation. Participants in the study included six ICT teachers enrolled in the “Embedded Systems and Robotic Applications” course of Spring 2018. A design-based research approach was used in order to achieve a systematic but flexible methodology. Within the scope of this study, robotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Banaeian and Gilanlioglu ( 2021 ) identified novelty as a factor that motivated the students to learn. Similarly, Uzun ( 2020 ) found that the motivation levels of students increased after attending classes involving robots. In Corsby and Bryant ( 2020 ), Gleason and Greenhow ( 2017 ), and Shaw et al ( 2018 ), the participants appreciated how the use of robots allowed remote learning.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Banaeian and Gilanlioglu ( 2021 ) identified novelty as a factor that motivated the students to learn. Similarly, Uzun ( 2020 ) found that the motivation levels of students increased after attending classes involving robots. In Corsby and Bryant ( 2020 ), Gleason and Greenhow ( 2017 ), and Shaw et al ( 2018 ), the participants appreciated how the use of robots allowed remote learning.…”
Section: Resultsmentioning
confidence: 90%
“…After removing the duplicates, 2065 articles were selected for analysis based on their titles and abstracts. Among these articles, 158 were retrieved for full-text screening, of which 28 articles (Abe et al, 2018 ; Aroca et al, 2013 ; Banaeian & Gilanlioglu, 2021 ; Corsby & Bryant, 2020 ; Cruz-Martín et al, 2012 ; Donnermann et al, 2020 , 2021 ; Gleason & Greenhow, 2017 ; Gomez-de-Gabriel et al, 2011 ; Guo et al, 2014 ; Gyebi et al, 2017 ; Ibrahim et al, 2020 ; Kurniawan et al, 2018 ; Li et al, 2016 ; Lister et al, 2018 ; Molloy et al, 2016 ; Rosenberg-Kima et al, 2020 ; Sampsel et al, 2011 ; Scott et al, 2020 ; Shaw et al, 2018 ; Shimaya et al, 2021 ; Suárez-Gómez & Pérez-Holguín, 2020 ; Sun et al, 2017 ; Uzun, 2020 ; Ververi et al, 2020 ; Wang et al, 2021 ; Winkelmann & Eberman, 2020 ; Wong et al, 2021 ) matched the inclusion criteria and were eventually retained for this study. Figure 1 illustrates the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%